The wisdom of animals : creatureliness in early modern French spirituality - Randall, Catharine, 1957- (University of Notre Dame Press, 2014)
Randall explores the link between philosophical and theological discussions of the nature and status of animals vis-à-vis the rest of existence, particularly humans.